Pengaruh Disiplin Kerja dan Efikasi Diri terhadap Prestasi Kerja yang di Moderasi oleh Motivasi Kerja pada Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara - Saskia, Saskia; Sunaryo, Sunaryo; Shofia, Aya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine Work Discipline and Self-Efficacy on Work Performance with Work Motivation as a moderating variable at the North Sumatra Province Industry and Trade Service. This research uses smartpls 4 as an analytical tool to determine the variables studied and justify how significantly the influence of the independent and dependent variables strengthens or weakens them. In this research, Structural Equation Modeling (SEM) was used with the Partial Least Square (PLS) method. In this study, the entire sample population was 155 employees at the North Sumatra Province Industry and Trade Department. The results of this research show that work discipline has a positive and significant effect on work performance. Self-efficacy has a positive and significant effect on work performance. Work motivation has a significant positive effect on work performance, negative work motivation does not significantly moderate self-efficacy on work performance, positive work motivation significantly moderates work discipline on work performance